Emotional factors that influence the development of speaking skills in post-pandemic classes in third baccalaureate students. - Eusebio Merchán, Lesly Katherine (2023)
This research project was conducted with the purpose of analyzing the influence of emotional factors on the development of speaking skills in post-pandemic classes with third-year high school students. Identifying these factors helped us to analyze emotional factors such as nervousness, anxiety, low self-esteem, fear of making mistakes, and lack of confidence in speaking activities during English classes. The design of this research was designed for third year high school students and we focused on a specific course that showed to have students with these problems in order to analyze the emotional factors and how it affects the development of speaking skills. Based on the results obtained from this research, it can be concluded that the emotional factors that affect the students are mostly nervousness and fear of making mistakes. Despite this, the students are positive in wanting to improve their skills and knowledge in the English language because they show a motivation that is shared among classmates and understand that making mistakes or receiving corrections from the teacher helps them to obtain better knowledge in aspects such as pronunciation or grammar. Therefore, emotional factors affect students in the acquisition of a foreign language and in the development of foreign language skills, but with a pleasant classroom environment, motivation, and peer support, these emotional factors are reduced, and positive aspects of learning are increased.